Pengaturan Pemanfaatan Ruang di Kawasan Pesisir Pantai Provinsi Sumatera Barat: Analisis Peraturan Daerah Kota Padang Nomor 14 Tahun 2012 tentang Rencana Tata Ruang Wilayah Kota Padang Tahun 2010-2020 - Rosari, Anton (Jurnal Kepastian Hukum dan Keadilan, 2021)
Pariaman City Regional Regulation Number 21 of 2012 concerning Pariaman City Spatial Planning 2010-2020, South Coastal Regency Regulation Number 7 of 2011 concerning South Coastal Regency Spatial Planning 2010-2020, based on West Sumatra Province Regional Regulation Number 12 Year 2018 concerning the Zoning Plan for Coastal Areas and Small Islands of West Sumatra Province for 2010-2030. The research method used is prescriptive normative. This regulation is part of Spatial Planning management which consists of Planning, Organizing, Actuating, and Control/Monitoring (POAC). Based on this regulation, the Government Authorities in the City and Regency and Provincial Governments are formed. This authority has been carried out according to the rules, but from the substance of the Planning there is still no detailed Spatial Plan for the city and district, so this can result in inadvertence in granting permits and development.Keywords: Coastal Area, Government, Spatial Planning, Regional Regulation